The impact of economic strain on life satisfaction in Taiwan - Wu, Feng-Tzu (International journal of economic perspectives, 2026)
This study examines the impact of high inflation and surging food prices in 2022–2023 on food-related satisfaction and overall life satisfaction among Taiwanese consumers. Given Taiwan’s heavy reliance on imports (over 90 % of goods), global supply shocks, particularly those triggered by the Russia-Ukraine war, translated directly into sharp increases in living costs. Using a nationwide online survey of 1,069 valid respondents conducted in December 2023, the research reveals a broad decline in both food-related and overall life satisfaction. The negative effects are significantly stronger among men, younger individuals (≤30 years), corporate employees, and university graduates, who face heightened financial pressure, job stress, and unmet expectations. Conversely, women report relatively higher satisfaction, attributing it to greater appreciation of food quality, family relationships, and adaptive household management during economic hardship. These findings enrich the understanding of consumer resilience under economic strain and offer actionable insights for policymakers and businesses aiming to mitigate the well-being costs of inflation in import-dependent economies.